Problems of legal regulation of platform employment in the Republic of Kazakhstan - Nurgaliyeva Енлик; Baimakhanova Аружан (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article discusses the problems of legal regulation of platform employment in the Republic of Kazakhstan. Since platform employment in the country is in its infancy, not only the issues of interaction between the platform and all persons who participate in its activities remain unresolved, but also the issues of adapting labor relations to the realities of the digital economy. Having analyzed the acts of international organizations, and the works of academic economists and lawyers, the authors conclude that the new norms of the Social and Labor Codes do not sufficiently consider the existing relations in platform employment and groundlessly establish the priority of civil legislation. It is noted that the legal relations that develop in this case have characteristics of both labor and civil law. The experience of some countries that have managed to secure the status of workers within the framework of labor law for platform workers is also presented. It is also concluded that at present there is a need to adapt labor relations to the realities of the digital economy, to also legislate the concepts of “employee”, “employer”, and “labor relations” to prevent the infringement of the labor rights of platform workers.